Management - Drucker, Peter F. (Peter Ferdinand), 1909-2005.; Maciariello, Joseph A. (New York, NY : Collins, 2008)
The essential book on management from the man who invented the discipline now completely revised and updated for the first time.
Introduction to the revised edition of Management: Tasks, Responsibilities -- Preface -- Introduction: management and managers defined -- Management as a social function and liberal act -- The dimensions of management -- Management's new realities -- Management's new realities Part I -- Knowledge is all -- Management's new realities part II -- New demographics -- The new realities Part III -- Future of the corporation and the way ahead -- Management's new paradigm -- Business performance -- The theory of business -- The purpose and objective of a business -- Making the future today -- Strategic planning: the entrepreneurial skill -- Performance in service institutions -- Managing service institutions in the society of organizations -- What successful and performing nonprofits are teaching business -- The accountable school -- Rethinking "reinventing government" -- Entrepreneurship in the public-service institution -- Productive work and achieving worker -- Making work productive and the worker achieving -- Managing the work and worker in manual work -- Managing the work and worker in knowledge work -- Social impacts and social responsibilities -- Social impacts and social responsibilities -- The new pluralism: how to balance the special purpose of the institution with the common good -- The manager's work and jobs -- Why managers? -- Design and content of managerial jobs -- Developing management and managers -- Management by objectives and self-control -- From middle management to information-based organizations -- The spirit of performance -- Managerial skills -- The elements of effective decision making -- How to make people decisions -- Managerial communications -- Controls, control, and management -- The manager and the budget -- Information tools and concepts -- Innovation and entrepreneurship -- The entrepreneurial business -- The new venture -- Entrepreneurial strategies -- Systematic innovation using windows of opportunity -- Managerial organization -- Strategies and structures -- Work- and task-focused design -- Kinds of teams -- Result- and relation-focused design -- Alliances -- The CEO in the new millennium -- The governance of the corporation -- New demands on the individual -- Managing oneself -- Managing the boss -- Realizing oneself -- seven personal experiences -- The educated person -- Conclusion: the manager of tomorrow -- Bibliography -- Drucker annotated bibliography -- About Peter F. Drucker -- About the Peter F. Drucker Institute -- Index.
Includes bibliographical references (pages 529-549) and index.
Keywords: Management; Management